Pelaksanaan Praktik Kemahiran Hukum I di Pengadilan Negeri Buntok Kelas II - Lingga Abi Rahman; Muhammad Maulana Nazril; Jeora Nitysa Aprily; Erdha Aisha Chandia; Meysarah Meysarah; Dicky Juliandi; M. Faishal Fadhlurrahman; Luqman Hakim; Aris Sunandar (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the role and function of the Buntok Class II District Court in carrying out the judicial process in Indonesia, focusing on its organizational structure, main duties, functions, and the challenges faced by the institution. Using methods of direct interviews and literature studies, the author is able to gather in-depth information about the court's operations and the challenges it faces, such as limitations in facilities and staff training. This article also explores moot court as part of internship activities aimed at honing students' legal skills. The findings provide a deeper understanding of the importance of improving infrastructure and staff competency development to enhance the quality of local judiciary services.